2013
DOI: 10.1002/jgre.20108
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional numerical modeling of the Rheasilvia impact formation

Abstract: [1] We numerically modeled the formation of Rheasilvia crater, an enormous impact basin centered on asteroid 4 Vesta's south pole. Using a trial and error method, our models were adjusted to produce the best possible fit to Rheasilvia's size and shape, as observed during the Vesta orbital stage of the Dawn mission. The final model yields estimates of the shock wave decay, escaped material volume, depth of excavation, and other relevant characteristics, to the extent allowed by the two-dimensional (axially symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 30 publications
8
45
0
Order By: Relevance
“…The combined mass of the vestoids is consistent with (i.e., lower than) the amount of material estimated to have been excavated by the Rheasilvia and/or Veneneia impacts (Schenk et al, 2012;Moskovitz et al, 2008;Ivanov and Melosh, 2013), and the spectra of vestoids match those of Vesta (e.g., Binzel and Xu, 1993). Marzari et al (1999) calculated that the observed steep size distribution of vestoids would have been reduced to match the background asteroid population if the Vesta family were older than $1 Ga, and the tight clustering of vestoid orbital elements supports this age constraint (Nesvorny et al, 2008).…”
Section: Absolute Agessupporting
confidence: 69%
See 1 more Smart Citation
“…The combined mass of the vestoids is consistent with (i.e., lower than) the amount of material estimated to have been excavated by the Rheasilvia and/or Veneneia impacts (Schenk et al, 2012;Moskovitz et al, 2008;Ivanov and Melosh, 2013), and the spectra of vestoids match those of Vesta (e.g., Binzel and Xu, 1993). Marzari et al (1999) calculated that the observed steep size distribution of vestoids would have been reduced to match the background asteroid population if the Vesta family were older than $1 Ga, and the tight clustering of vestoid orbital elements supports this age constraint (Nesvorny et al, 2008).…”
Section: Absolute Agessupporting
confidence: 69%
“…The relative youth of the Vesta family asteroids is also consistent with a recent age estimate (Milani et al, in press) based on study of asteroid orbital dynamics. Conversely, other workers (Moskovitz et al, 2008;Ivanov and Melosh, 2013) suggest that there is an apparent deficiency in volume of the observed vestoids that is consistent with dynamical depletion and collisional grinding over $3.5 Ga. Furthermore, dynamical analysis of basaltic main belt asteroids suggests a minimum age of 1 Ga under specific circumstances for the V-type asteroids separated from the main Vesta family (Nesvorny et al, 2008).…”
Section: Absolute Agessupporting
confidence: 64%
“…At greater depth, olivine rich mantle and a metal core are expected (Righter and Drake, 1997b). McSween et al (2013b) suggest a thickness of the eucritic crust in the range of 10-20 km, which is distinctly lower than the expected excavation depth of the Rheasilvia impact event of about 30-45 km (Ivanov and Melosh, 2013;Jutzi and Asphaug, 2011). Thus, a significant amount of mantle material is suspected to be excavated by this impact event.…”
Section: Discussion -Implications For the Vesta's Interiormentioning
confidence: 88%
“…They also often enclose material excavated from greater depth of the target body reflecting possible compositional differences of the crustal material. Large impacts like Rheasilvia and Veneneia probe Vesta's internal structure to the depth of the order of several tens of km (Ivanov and Melosh, 2013;Jutzi and Ivanov, 2014;Jutzi et al, 2013). With Vesta expected to be a differentiated object with a crust and mantle of different composition (McSween et al, 2013a), the ejecta emplaced during these impact events should display these compositional differences depending on the distance of their location from the impact crater (Osinski et al, 2011).…”
Section: Implications For the Stratigraphymentioning
confidence: 97%
“…Hydrocode simulations also revealed subsurface damage caused by impacts on asteroids (e.g., Asphaug, 1997;Nolan et al, 2001;Buczkowski et al, 2012;Bowling et al, 2013aBowling et al, , 2013bIvanov and Melosh, 2013). Asphaug et al (1996) used the hydrocode SALE2D (Amsden et al, 1980) to examine subsurface damage on the asteroid Ida, and Asphaug (1997) provided similar analysis for the asteroid 4 Vesta.…”
Section: Introductionmentioning
confidence: 97%